Avoiding Error and Finding the Right Balance in European Health Technology Assessments: Insights Generated by the European Access Academy - Elaine Julian; Tom Belleman; Maria João Garcia; Maureen Rutten-van Mölken; Robin Doeswijk; Rosa Giuliani; Bernhard J. Wörmann; Daniel Widmer; Patrick Tilleul; Ruben Casado Arroyo; Valentina Strammiello; Kate Morgan; et al. (Journal of Market Access & Health Policy)
Background: We examined four potential challenges for the implementation of the European Union (EU) Regulation 2021/2282 on Health Technology Assessment (EU HTAR): interaction with the European Medicines Agency (EMA), expert input, the interface of European health technology assessment (EU HTA) joint procedures with those within Member States, and the management of conflict of interest. This research aims to explore how to address these challenges in a balanced manner and prioritise key actions for effective collaboration in the context of the EU HTA. Methods: The methodology included a pre-convention survey among relevant stakeholders as well as working groups and the plenary ranking of discussion outcomes at the European Access Academy (EAA) Spring Convention 2024. Results: In the survey, 65.5% of respondents indicated that experts are currently not sufficiently included in the upcoming joint scientific consultations and clinical assessments; only 37.9% suggested that the EU HTA joint procedures would accelerate national appraisal decision-making, and 58.6% believed that the principles of ‘transparency’ and ‘competency’ are balanced in the EU HTA position on conflict of interest. The top priority action points identified in the working groups were the involvement of the best available expertise, the early and inclusive involvement of experts, strengthened early scientific dialogue, and the fostering of the political willingness/financial support of EU Member States to increase capacities. Conclusions: The key topics identified were an approach to conflict of interest that balances transparency obligations and the need for expertise, strengthens the involvement of clinical and patient experts, intensifies early interaction between the EMA and EU HTA, and increases the involvement of the EU Member States.